"My mom calls it Annaland": A Qualitative Study of Phenomenology, Daily Life Impacts, and Treatment Considerations of Sluggish Cognitive Tempo. Issue 6 (April 2022) - Becker, Stephen P.; Fredrick, Joseph W.; Foster, Josalyn A.; Yeaman, Kiley M.; Epstein, Jeffery N.; Froehlich, Tanya E.; Mitchell, John T.
Objective: To conduct qualitative analysis of interviews to understand phenomenology, daily life impact, and treatment considerations of sluggish cognitive tempo (SCT) behaviors in children and adolescents.Method: Youth with elevated SCT symptoms ( N  = 15, ages 9–16 years) and their parents completed interviews focused on their perception and daily life impact of SCT behaviors. Parents were also asked about intervention targets.Results: Parents and youth had both negative and positive perceptions of SCT, with SCT fostering creativity/imagination and a break from stressors while also negatively impacting daily functioning. The domains most frequently selected by parents as SCT intervention targets were academics, emotions, mind wandering, morning routines, and self-esteem.Conclusion: Children and their parents share negative and positive views of SCT behaviors, while also detailing specific ways that SCT negatively impacts day-to-day functioning. This study offers insights into possible intervention targets as provided by youth and parents directly impacted by SCT.